The Dependency of Supply Chain Management and Product Quality on Product Innovation - Mochamad Yudha Febrianta; Muhammad Indra; Sri Widianesty (Budapest International Research and Critics University, 2021)
One of the challenges faced by fashion MSMEs (Micro, Small and Medium Enterprises) in Bandung is the poor quality of their products. Product quality is one of the important aspects to consider while aiming for strengthening competitiveness and customer satisfaction. Therefore, the fashion MSMEs need to continuously improve their product quality to be better and more reliable in order to gain consumer’s trust and satisfaction. Supply chain management has been proven to affect product quality. On the other hand, product innovation is also needed to ensure continuous improvement in product quality. This study applied a quantitative method to analyze the direct and indirect influence of supply chain management on product quality. The indirect influence used product innovation as an intermediating variable. The data were collected by distributing questionnaires among fashion MSMEs in Bandung area and processed by using SmartPLS 3.2.8. The inner model, outer model and bootstrapping were produced in data processing to identify the root causes of the problem based on the phenomena raised in this study. The analysis results showed that supply chain management has significant effects on product quality. Product innovation as a mediating factor also significantly affects the relationship between supply chain management and product quality. This study contributes as references for fashion MSMEs to improve their product quality through supply chain management and product innovation to achieve competitive advantages and high customer satisfaction rates.